Performance Analysis of Effect of Electric Field on Single-Wall Carbon Nanotubes as VLSI Interconnects - Kaur, Harsimran (My University, 2014)
For more than 30 years, the rate at which performance of silicon integrated circuits (IC) has improved is astonishing. The number of functions per chip has grown exponentially, thus dramatically scaling the IC which is threatened by physical limitation of copper-based electrical wires. To alleviate this problem, the most potential candidate for future ICs is carbon-nanotube (CNT) based interconnect schemes. CNT interconnects has the advantage of having a large electron mean free path, hence low resistance than copper interconnects. As interconnect material single-wall CNT (SWCNT) having higher conductivity is more preferable to the relatively lower conductivity multi-wall CNT (MWCNT). The high resistance associated with an isolated SWCNT necessitates the use of a bundle of SWCNTs. In this dissertation an efficient circuit-compatible RLC model for metallic SWCNT bundle is presented. Using this model, the performance of SWCNT-bundle interconnects is compared to copper wires. Results show that the bundles of SWCNTs having smaller value of signal delay and power delay product (PDP) achieve significantly better performance than copper interconnects at scaled technologies. Thus, SWCNT bundles can outperform copper for long intermediate and global interconnects. Influence of electric field on single walled carbon nanotube (SWCNT) bundle interconnects is studied in order to explore the electrical properties of SWCNT bundle. Voltage dependent equivalent circuit model is presented that capture various electron–phonon scattering mechanisms as a function of electric field. To estimate the performance of SWCNT bundle interconnects, signal delay and power dissipation is calculated based on field dependent model that results in improvement in the delay and power estimation accuracy compared to field independent model. Power delay product (PDP) of interconnect decides whether it has potential of being a reliable interconnect for the given technology. It is observed that power delay product of SWCNT bundle increases with increase in electric field but decreases with technology scaling showing that in low electric field regime, SWCNT bundle is a reliable alternative interconnect for future technologies in a high performance VLSI industry.
M.Tech. (VLSI Design)
Keywords: SWCNT; MWCNT; Electric Field; Mean Free Path